COVID-19: The need of an integrated and critical view - El-Hani, Charbel N.; Machado, Virgílio (Ethnobiology and Conservation, 2020)
To understand and act upon a complex reality like COVID-19, we need to integrate knowledge from different academic sciences, in interdisciplinary efforts, and academic knowledge and other knowledge systems, in transdisciplinary processes. Without an integrated view leading to socially robust orientations, we are less likely to successfully navigate our challenging times. However, COVID-19 became a “wicked problem”, in which there is broad disagreement on what the very ‘problem’ is, and instead of a “whole-of-government, whole-of-society approach”, we find partial solutions that fall short of dealing with the complex dilemmas posed by the wicked problem. To build an integrated view, different scientists and social actors should engage in trust relationships and accept mutual epistemic dependencies, as requisites for a concerted way of understanding and acting on the problem. This is particularly hard, however, in a wicked problem. In building an integrated view on COVID-19, the role of academic sciences should be surely recognized, but we should avoid turning this recognition into an advocacy for scientism. It remains necessary to recognize and value the plurality of knowledge systems that span over human history, as well as their integration for mutual learning and concerted action. It is worth briefly examining, then, an integration initiative in COVID-19 treatment, namely between traditional Chinese and Western medicine. Finally, an integrated and critical view of COVID-19 demands that we cast aside the myth of value-free science, consider the relationships between values and scientific work, and conceive how knowledge can be objective without being neutral.